2009
DOI: 10.1136/aim.2008.000075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Electroacupuncture on Postoperative Pain, Analgesic Requirements, Nausea and Sedation: A Randomised Controlled Trial

Abstract: Background: Acupuncture has potential value in producing analgesia in the postoperative period, but previous trials have inconsistent results. We aimed to study the effect of electroacupuncture on pain and nausea and the requirement for postoperative analgesia via patientcontrolled analgesia. Method: 107 patients who were undergoing abdominal hysterectomy or laparascopic cholecystectomy were randomised to receive either electroacupuncture (n = 56) or no additional treatment (n = 46) during the operative period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…12 One possibility for the negative fi ndings of a recent study 26 on the use of EA during surgery was the use of a single frequency of higher stimulation (10 Hz). The use of a single frequency favours neuronal accommodation, reducing its therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…12 One possibility for the negative fi ndings of a recent study 26 on the use of EA during surgery was the use of a single frequency of higher stimulation (10 Hz). The use of a single frequency favours neuronal accommodation, reducing its therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The use of adhesive tapes on all acupuncture sites of all patients was also designed to ensure that neither the patients nor the staff caring for them knew which treatment was given to each patient. 18 Also, we could ask patients afterwards if they understood to which group they belonged. The measurements could have been continued for an additional 24 h.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that an extended treatment time and the selection of different acupoints (particularly in the form of combined points) might offer more promising results. Previous studies indicated that stimulation on the acupoint Neiguan (P6) was an effective anti-emetic technique for the prevention of CINV [18, 19], and stimulation on the acupoints Zusanli (ST36) and Hegu (LI4) showed similar results [20–23]. Stimulation on two or more acupoints may improve anti-emetic efficacy, but it lacks the support of clinical trial data.…”
Section: Introductionmentioning
confidence: 99%